Complexity and Incompleteness in the ‘Interactive’ Conception of Knowledge - Roberta Corvi (Humana.Mente: Journal of Philosophical Studies)
This contribution aims in the first part at identifying the origin of the problem for which an “interactive” view of knowledge is offered as a solution. In the second part, it examines the features of knowledge understood in this way, noting the difficulties inherent in such an idea, which, however, do not invalidate the overall value of our hypotheses and theories. In the third and final part, the paper discusses some explicit or implicit aspects of the “interactive” view, which, as Parrini himself stated in his recent writings, has interesting points of contact with a systemic and transdisciplinary approach.